MOF‐Derived Potassiophilic CuO Nanoparticles on Carbon Fiber Cloth as Host for Stabilizing Potassium Metal Anode. Issue 3 (9th February 2022) - Liu, Shuang; Yang, Yujie; Qian, Yang; Chang, Ge; Zhao, Xin; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: Potassium (K) metal anodes suffer the main obstacle of uncontrollable dendrite growth. One of the best ways to overcome this challenge is to build a stable potassiophilic host. Herein, we designed a Metal‐Organic Frameworks (MOF)‐derived CuO nanoparticles on carbon fiber cloth (CC) as a high potassiophilic host to prestore molten potassium for dendrite‐free K metal anode. The three‐dimensional host has a relatively large surface area and excellent mechanical strength, which helps to lower the local current density as well as buffer the volume expansion during the plating/stripping of K. The highly potassiophilic CuO nanoparticles could provide abundant nucleation sites for K, thereby guiding uniform K deposition with a low nucleation overpotential and inhibits the growth of dendrites. The CC@CuO@K anode could cycle for 2000 h at a current of 0.5 mA cm −2, which exceeds K metal anodes mentioned in other reports. Last but not least, by using the composite K metal as the anode to assemble the full cell, highly boosted performance can be achieved. Our result provides a tempting method for realizing dendrite‐free K metal anodes in PIBs, and also provides an opportunity for the application of other MOF‐based materials in the field of high‐performance K metal anodes. Abstract : Suppressing dendrite growth : Cu‐MOF is loaded onto the carbon fiber cloth (CC@Cu‐MOF) as the precursor of CuO by simple hydrothermal heating. After carrying out the thermal treatment at 450 °C in the air, the sample obtained is directly used to permeate molten K. The obtained CC@CuO@K composite anode achieves a long‐term cycling stability of 2000 h in symmetric cells.